Perbandingan Keanekaragaman Dan Pemanfaatan Family Zingiberaceae Dalam Kehidupan Suku Jawa Dan Suku Dayak - Nurhazizah Nurhazizah (Jurnal Biologi dan Pembelajarannya (JB&P), 2021)
This study aims to explore deeper information regarding the comparison of the diversity and utilization of medicinal plant species from the Zingiberaceae family owned by the Javanese and Dayak tribes. The method used is a literature study by collecting data from books, journals, scientific articles, literature reviews containing the concepts studied. The results of research samples taken from 6 regions of the Javanese and 6 regions of the Dayak tribe showed a total of 40 species of the Zingiberaceae family found in the Javanese and 28 in the Dayak. The highest utilization used by the Javanese is turmeric (Curcuma domestica). . While the highest utilization used by the Dayak people is ginger (Zingiber officinale). Medicinal plants of the Zingiberaceae family that are used by the Javanese and Dayak tribes have various benefits. The part used for medicine is the rhizome.